PERAN MATA KULIAH KERJA PRAKTEK PADA TUGAS AKHIR MAHASISWA TEKNIK ARSITEKTUR DI JAKARTA - Kiki Maria (Fakultas Teknik Universitas Pancasila, 2020)
Abstract Practical work is one of the requirements for taking the final project (thesis) in the Architectural Engineering Study Program. Practical Work Performed by students majoring in Architecture for approximately four (4) months to carry out activities on certain construction projects that are related to the field of architecture such as planning, implementation and supervision of institutions outside the campus in this case the Contractor or Planning Consultant. This research is to find out whether students in carrying out the Final Project also apply the experience gained while carrying out practical work. Based on the above background, we are very interested in proposing and trying to do research with the title